Capsular polysaccharide of Mycoplasma mycoides subsp. capri contributes to phenotypic diversity promoting distinctive immune responses - Yimthin, Thatcha; Bourgeon, Marilou; Zhang, Jing; Eggerschwiler, Lukas; Siegenthaler, Raphael; Schieck, Elise; Torres-Puig, Sergi; Ruggli, Nicolas; Démoulins, Thomas; Jores, Joerg (PLOS Pathogens, 2025)
Author summary Mycoplasmas are cell-wall deficient minute bacteria that encompass important human and animal pathogens. Despite the absence of classical virulence factors such as toxins in many pathogenic mycoplasmas, the later can cause severe infectious diseases, including life-threatening pleuropneumonia or septicemia. The clinical disease is often associated with massive inflammation of affected tissues. It is well known that mycoplasmas can vary their surface protein expression, which contributes to phenotypic diversity and immune evasion. Several pathogenic mycoplasmas are known to possess a capsule. This article reports the ability of Mycoplasma mycoides subsp. capri, to switch the expression of capsular polysaccharide on and off, which profoundly influences immune responses in its natural ruminant hosts. The presence of capsulated as well as capsule-deficient mycoplasmas in the host adds another layer to phenotypic diversity and promotes different host immune responses that likely foster the dissemination, inflammation and pathogen persistence commonly observed during infections with mycoplasmas.